Transformation of Islamic Higher Education: Policy Strategy, Challenges, and Opportunities - Sumiati, Endang; Sutrisno; Sibawaihi; Tekke, Mustafa (LETIGES, 2024)
This study aims to identify policy strategies, research trends, challenges, and opportunities to transform Islamic Religious Higher Education (PTAI) to increase global competitiveness and relevance. This study uses a qualitative paradigm with a literature study approach to analyse the institutional transformation of Islamic higher education. Data were collected by searching for scientific articles in leading databases, such as Scopus and Garuda Kemendikbud. The analysis used content analysis techniques to identify central themes and synthesise data descriptively. The study's results identified several important aspects related to policy strategies, research trends, and challenges and opportunities, including (1) Digital Transformation of Islamic Education, where PTAI needs to develop a curriculum that is in line with technology and ensure that the quality of teaching is maintained. The Diffusion of Innovation Theory explains that factors such as relative advantage, observability, complexity, trialability, and technology compatibility influence the adoption of technology in PTAI; (2) A sustainable Adaptive Education Model based on transformational learning theory, which emphasises the importance of critical reflection on social and environmental changes in order to prepare students to face global challenges; (3) Development of Digital Skills to support the transformation of higher education, by the Theory of Educational Technology; (4) Innovation and Entrepreneurship that focuses on increasing the competitiveness of PTAI, based on the theory of educational entrepreneurship. The implications of this study indicate that PTAI needs to adopt technology and adaptive education models to increase global competitiveness. The study's limitations lie in the limited library sources of international scientific articles. The suggestion for further research is to explore the practical implementation of PTAI transformation in various countries, focusing on field studies.